Ultrasound‐guided intracardiac xenotransfusion of canine packed red blood cells and epinephrine to the left ventricle of a severely anemic cat during cardiopulmonary resuscitation. Issue 2 (10th January 2017) - Oron, Liron; Bruchim, Yaron; Klainbart, Sigal; Kelmer, Efrat
Abstract: Objective: To describe the use of an ultrasound‐guided intracardiac xenotransfusion of canine packed red blood cells (pRBC) to the left ventricle of a severely anemic cat during cardiopulmonary resuscitation (CPR). Case Summary: An 8‐year‐old previously healthy neutered female cat was presented with severe weakness after she had disappeared for 1 month. On presentation, the cat was in hypovolemic shock, laterally recumbent, and severely anemic with massive flea infestation. Within minutes of admission, the cat became agonal and suffered cardiopulmonary arrest. CPR was immediately initiated; however, attempts to gain IV access during CPR were unsuccessful. As the cat's blood type was yet unknown, 10 mL of canine pRBC was transfused directly into the left ventricular chamber using ultrasound guidance, as well as 0.02 mg/kg of epinephrine using a similar technique. The cat regained cardiac activity and once the jugular vein was cannulated it received 20 additional mL of canine pRBC intravenously. The packed cell volume and total plasma protein following the intracardiac transfusion were 0.09 L/L [9%] and 30 g/L [3.0 g/dL], respectively. Subsequent blood typing revealed the cat had type B blood. The cat was discharged 3 days post‐CPR and was alive and doing well 3 months following discharge. New or Unique Information Provided: This is the first reported case of ultrasound‐guided intracardiac canine‐to‐feline xenotransfusion during CPR.